Comparison of The Effect of Genetic and Intake on Stunting Incidence in Toddlers - Andi Eka Yunianto; Dika Betaditya; Yana Listyawardhani (Sarana Ilmu Indonesia (salnesia), 2023)
The prevalence of stunting in children under five is influenced by genetic factors and nutritional status originating from direct nutritional intake. This study aims to determine the contribution of genetic factors and food intake to the occurrence of stunting in toddlers in the Rajapolah Community Health Center area. This research used an observational methodology with a case-control design involving a total of 66 toddler participants. Among them, 33 people were identified as having stunting (with height-for-age Z-score < -2 SD), while 33 people had normal nutritional status (height-for-age Z-score => -2 SD). The participants were selected using purposive sampling. Data analysis includes applying the unpaired T test for normally distributed data, as well as the Mann-Whitney test for non-normally distributed data. The results of this investigation highlight significant differences in genetic aspects of height (both father and mother) between the stunted and non-stunting toddler groups (with p values of 0,029 and 0.046, respectively). In addition, nutritional intake, including energy (p-value<0,001), protein (p-value<0,001), fat (p-value=0,01), and carbohydrates (p<0,001), was between the two groups. Based on these findings, it can be concluded that genetic factors (in the form of parental height) and nutritional intake (including energy, protein, fat and carbohydrates) have a significant influence on the occurrence of stunting in toddlers. Therefore, this research is a basis for designing interventions aimed at mitigating the problem of stunting within the operational scope of the Rajapolah Community Health Center.